Analisis Kesantunan Berbahasa dalam Pementasan Wayang Climen Lakon Semar Kelangan Wadhag dan Relevasinya sebagai Materi Ajar Memahami Isi Teks Cerita Mahabharata di SMA - Nugroho, Benny Setyo Adi; Wijayanti, Kenfitria Diah; Suryanto, Edy (Universitas Sebelas Maret, 2022)
This research aims to disseminate. (1) Principle of language politeness on the staging of puppet climen play Semar Kelangan Wadhag, (2) a form of violation of the principle of language politeness in the staging of puppet climen play Semar Kelangan Wadhag and (3) Relevance of the results of analysis of puppet performance climen play Semar Kelangan Wadhag as an alternative teaching material understanding the contents of the mahabharata story text class X even semester. This type of research is a descriptive analysis. The method used in collecting this research data is to check and do the transcript process on the staging of puppets of semar Kelangan Wadhag to produce manuscripts (texts). The next process is data identification, and finally data reduction is carried out. The validity of data is derived from the process of triangulation of data sources, observations, and theories. The results : (1) a form of the principle of language manners in the performance of puppet climen play Semar Kelangan Wadhag in accordance with Geoffrey Leech's principle of (a) maksim wisdom, (b) maximal mercy, (c) maximality, (d) maximal acceptance, (e) maksim humility, and (f) maximal fit. The principle of the dominant language manners in this story is the maxim, because in this story the puppeteer emphasizes to always be wise in overcoming all problems. (2) The form of violation of the principle of politeness in this story is dominant in the maxim of acceptance or appreciation of a number of 5 (five) data, because in this story there are many conflicts that demean the opposing figure. (3) Relevance of the results of the analysis of puppet performance climen play Semar Kelangan Wadhag as an alternative teaching material to understand the contents of the mahabharata story text class X even semester. After analysis and interviews in this study can be used as teaching material to understand the contents of the mahabharata story text of class X even semester. With the puppet climate, it provides a new color for learning material with a short duration but still contains the moral values contained in the puppet performances that are played, because this play contains moral values and character and is by today's conditions.